Validation of the Social Appearance Anxiety Scale in Patients With Systemic Sclerosis: A Scleroderma Patient‐Centered Intervention Network Cohort Study. Issue 10 (27th September 2018) - Mills, Sarah D.; Kwakkenbos, Linda; Carrier, Marie‐Eve; Gholizadeh, Shadi; Fox, Rina S.; Jewett, Lisa R.; Gottesman, Karen; Roesch, Scott C.; Thombs, Brett D.; Malcarne, Vanessa L.; ,
Abstract : Objective: Systemic sclerosis (SSc) is an autoimmune disease that can cause disfiguring changes in appearance. This study examined the structural validity, internal consistency reliability, convergent validity, and measurement equivalence of the Social Appearance Anxiety Scale (SAAS) across SSc disease subtypes. Methods: Patients enrolled in the Scleroderma Patient‐centered Intervention Network Cohort completed the SAAS and measures of appearance‐related concerns and psychological distress. Confirmatory factor analysis (CFA) was used to examine the structural validity of the SAAS. Multiple‐group CFA was used to determine whether SAAS scores can be compared across patients with limited and diffuse disease subtypes. Cronbach's alpha was used to examine internal consistency reliability. Correlations of SAAS scores with measures of body image dissatisfaction, fear of negative evaluation, social anxiety, and depression were used to examine convergent validity. SAAS scores were hypothesized to be positively associated with all convergent validity measures, with correlations significant and moderate to large in size. Results: A total of 938 patients with SSc were included. CFA supported a 1‐factor structure (Comparative Fit Index 0.92, Standardized Root Mean Residual 0.04, and Root Mean Square Error of Approximation 0.08), and multiple‐group CFA indicated that the scalar invariance model best fit the data. Internal consistency reliability was good in the total sample (α = 0.96) and in disease subgroups. Overall, evidence of convergent validity was found with measures of body image dissatisfaction, fear of negative evaluation, social anxiety, and depression. Conclusion: The SAAS can be reliably and validly used to assess fear of appearance evaluation in patients with SSc, and SAAS scores can be meaningfully compared across disease subtypes.